PENGEMBANGAN BAHAN PEMBELAJARAN DENGAN MENGGUNAKAN BUKU BERGAMBAR SEBAGAI MEDIA PEMEROLEHAN BAHASA INDONESIA - Jainatun Naimah Syamsiah (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
The objectives of this study are 1) to describe the acquisition of Indonesian language by means of picture books for elementary school children; 2) describe the development of picture books in accordance with the cognitive development of elementary school students.This research belongs to the type of development research or what is called research and development (R&D). Sources of research data are teachers, parents and first grade students of SD Negeri 068074 Medan. Data collection techniques using observation, questionnaires and interviews. The data analysis techniques used are qualitative and quantitative techniques The results of the acquisition of Indonesian for elementary school children consist of several stages, namely the pre-linguistic stage, the one-word stage, the two-word stage, and the many-word stage. The development of picture books in the study went through the stages of gathering information and it was known that there were problems in developing children's language acquisition due to the limitations of books and also the competence of teachers in teaching. The next stage is the preparation of the instrument and continued with the validation of the instrument that has been compiled, the results are that the instrument is suitable for use. The next stage is the development of book designs, namely teacher guidebooks and student books. The results of expert validation on the product showed that the average score for the assessment of the teacher's manual and student's book products was 3.98, so the book developed was suitable for use without revision. The next stage is product testing. The results of the teacher's guide book assessment get a score of 3.93 in the